Access to a guanacastepene and cortistatin-related skeleton via ethynyl lactone Ireland−Claisen rearrangement and transannular (4 + 3)-cycloaddition of an azatrimethylenemethane diyl - Zhurakovskyi, O; Ellis, S; Thompson, A; Robertson, J (American Chemical Society, 2017)
Heating a 2,5-furanocyclic (2-azidoethyl)allene initiates a cascade reaction comprising azide–allene cycloaddition, loss of nitrogen, and azatrimethylenemethane (ATMM) diyl–furan transannular (4+3)-cycloaddition. The major product of this reaction contains the pentacyclic core common to guanacastepenes D and H, and radianspenes J–L; in addition, the central oxabridged cycloheptene ring, flanked by two carbocyclic rings, is structurally related to the ABC-ring system found in the cortistatins. This is the first reported synthetic application of a ‘free’ (non-conjugated) ATMM. The cyclization precursors were prepared via the first reported examples of the Ireland–Claisen rearrangement of an ethynyl lactone.